Neurobiological, Cognitive, and Emotional Mechanisms in Melodic Intonation Therapy - Merrett, Dawn L.; Peretz, Isabelle; Wilson, Sarah J. (Frontiers in Human Neuroscience, 2014)
Singing has been used in language rehabilitation for decades, yet controversy remains over its effectiveness and mechanisms of action. Melodic Intonation Therapy (MIT) is the most well-known singing-based therapy; however, speculation surrounds when and how it might improve outcomes in aphasia and other language disorders. While positive treatment effects have been variously attributed to different MIT components, including melody, rhythm, hand-tapping, and the choral nature of the singing, there is uncertainty about the components that are truly necessary and beneficial. Moreover, the mechanisms by which the components operate are not well understood. Within the literature to date, proposed mechanisms can be broadly grouped into four categories: 1) neuroplastic reorganization of language function, 2) activation of the mirror neuron system and multi-modal integration, 3) utilization of shared or specific features of music and language, and 4) motivation and mood. In this paper, we review available evidence for each mechanism and propose that these mechanisms are not mutually exclusive, but rather represent different levels of explanation, reflecting the neurobiological, cognitive, and emotional effects of MIT. Thus, instead of competing, each of these mechanisms may contribute to language rehabilitation, with a better understanding of their relative roles and interactions allowing the design of protocols that maximize the effectiveness of singing therapy for aphasia.